"I actually just really need to stop work sometimes": Exploring fatigue‐related barriers to employment among people with rheumatic diseases. (23rd November 2018) - Helme, Caitlin; Hegarty, Roisin S.M.; Stebbings, Simon; Treharne, Gareth J.
Abstract: Purpose: Fatigue is a common symptom of many rheumatic diseases (RDs), but more research is needed to explore the experience of fatigue and its impact on employment among people with RDs. The aim of the present study was to investigate experiences of fatigue, its impact on employment and strategies that people with RD use to continue working. Method: Semi‐structured in‐depth interviews were conducted with five participants with a range of RDs living in New Zealand (three women, two men; aged 45–64 years). All participants were employed part time at the time of the interview. The transcripts were subjected to inductive thematic analysis, led by the first author, who had an RD. Results: Four themes resulted from the analysis: (a) workplace management and coping strategies; (b) the function of positive workplace relationships; (c) barriers to understanding; and (d) collectively improving understanding. These themes act to explain how individuals with RDs in employment believe fatigue to have a bearing on their work, how they manage fatigue at work, how they believe coworkers and employers perceive and manage their fatigue, and what they believe could improve the understanding of fatigue in workplaces. Conclusions: Individuals with RDs in employment describe fatigue as playing a substantial role in their experiences at work. This research expands on previous literature addressing barriers to employment in those with RDs by specifically addressing the relevance of fatigue. It is imperative to provide information to employers, and guidelines for employees with an RD who are experiencing fatigue should outline appropriate strategies for success at work.